LOWLAND TECHNOLOGY INTERNATIONAL SPECIAL ISSUE – FOREWORD – - H. Araki; S. Hayashi (International Association of Lowland Technology, 2007)
Lowlands imply regions having low elevation, which are particularly susceptible to climatic, sea water level and environmental changes. For example, global warming, which appears to be causing a rise in sea level, must ultimately affect the safety of coastal dikes and other coastal infrastructures, as well as threaten the water and ecological systems in lowland areas. Lowland regions are also particularly vulnerable to natural disasters. In 2004, several large earthquakes and Tsunami in the Asian region caused major damage in lowland areas. The importance of exploration of problems in lowlands has been recognized by researchers, planners, engineers and administrators all over the world.